Meeting Abstracts of the 6th Uludag Cardiology Summit, March 26-29, 2026, Bursa, Türkiye - 6th Uludag Cardiology Summit (The European Research Journal, 2026)
OP-1. Prognostic Value of the HALP Score for Predicting Left Ventricular Remodeling in STEMI Patients Undergoing Primary PCI OP-2. Short Term Clinical Outcomes and Predictors of Selective Left Bundle Branch Pacing OP-3. Association Between Delayed QRS Transition Zone and Diabetes Mellitus OP-4. Vasospastic Angina: A Case of Coronary Spasm Confirmed by Ergonovine OP-5. Cardiac Effects of Chronic Pyrethroid Exposure OP-6. Effect of SGLT-2 Inhibitors on MPV in Heart Failure Patients OP-7. Evaluation of Subclinical Myocardial Dysfunction in Cirrhosis Using 4D Strain Analysis OP-8. The Role of the Intermountain Risk Score in Predicting Coronary Artery EctasiaOP-9. Association Between Uric Acid to Albumin Ratio and No-Reflow Phenomenon in Patients with NSTEMI OP-9. Association Between Uric Acid to Albumin Ratio and No-Reflow Phenomenon in Patients with NSTEMI OP-10. Coronary Vasospasm Presenting as ST-Elevation Myocardial Infarction: A Case Report OP-11. Management of a Stripped Stent within a Dissected Coronary Lesion OP-12. Prognostic Utility of the Pan-Immune-Inflammation Value (PIV) in Predicting No-Reflow Among Patients Undergoing Primary PCI for STEMI OP-13. VARC-3 Outcomes of Myval, Portico, and Evolut-R in TAVI OP-14. Colchicine Aiding Recurrent Pacemaker Pocket Inflammation Management: A Case Report OP-15. Colchicine Use After Coronary Artery Stenting: One-Year Follow-Up Results OP-16. Drug-Coated Balloon-Only Strategy for Chronic Total Occlusion: A Prospective, Two-Center Study of 48 Patients OP-17. The Role of Pharmacological Cocktails in Preventing Radial Spasm and Complications During Percutaneous Coronary Intervention (PCI): A Clinical Study OP-18. Drug-Coated Balloon-Only Strategy in a True LCx–OM Bifurcation Lesion (Medina 1.1.1): Case Report with 12-Month Follow-Up OP-19. The Utility of Atherogenic Index of Plasma in Predicting in-Hospital Ischemic Stroke in Patients Undergoing Carotid Artery Stenting OP-20. A Case of Long QT Syndrome Presenting with Ventricular Arrhythmia OP-21. Can We Predict Reperfusion in ST-Elevated Myocard Infaction? OP-22. The Effect of Volume Overload on Ventriculo-Arterial Coupling in Hemodialysis Patients OP-23. Minimal Symptoms, Maximum Risk: Hidden Type A Dissection Accompanying an 81 mm Ascending Aortic Aneurysm OP-24. Comparative Efficacy of Single- and Dual-Defibrillator Orthogonal Electrical Cardioversion in Persistent Atrial Fibrillation OP-25. Complete Atrioventricular Block and Postpartum Cardiomyopathy in a Patient With c-TGA: A Case of Right-Sided Cardiac Resynchronization Therapy OP-26. Predictive Value of Systemic Immune-Inflammation Index for INOCA OP-27. Transcatheter Closure of Mitral Paravalvular Leak Developing After Mechanical Mitral Valve Replacement: A Case Report OP-28. Acute Coronary Syndrome After Anaphylaxis: Kounis Syndrome Case OP-29. Cardiac Lymphoma: A Rare Case Report OP-30. The Clinical Significance of the Plasma Atherogenic Index in Predicting Total Occlusion in Patients with Non-ST Elevation Myocardial Infarction OP-31. Prognostic Nutritional Index and Frailty After Ischemic Stroke: Mid-Term Follow-Up Results OP-32. Diagnostic Challenge in Cardiac AL Amyloidosis: When Imaging Speaks Louder Than Serum Biomarkers OP-33. Nightmare in the Cath Lab: LMCA Dissection OP-34. Association of Preoperative Serum Magnesium Levels and Acute Kidney Injury Following Thromboembolectomy in Acute Limb Ischemia OP-35. Could the Systemic Coagulation Inflammation Index Be a Predictor of Worse Outcomes After Carotid Endarterectomy? OP-36. The Role of Exocrine Pancreatic Insufficiency in Predicting Concomitant Carotid Artery Disease in Diabetic Patients Scheduled to Undergo Coronary Artery Bypass Grafting OP-37. Relationship Between TASC II Lesion Severity and Carotid Artery Stenosis: A Cross-Sectional Analysis OP-38. Hyponatremic Seizure in a Middle-Aged Woman on Spironolactone–Hydrochlorothiazide OP-39. An Unexpected Cause of Angina: Successful Percutaneous Closure of an Internal Mammary Artery–Left Atrium Fistula OP-40. Predictors of Isolated Nocturnal Hypertension in Non-obese Non-diabetic Individuals OP-41. The Impact of Guideline-based Treatment on In-hospital Outcomes in Infective Endocarditis OP-42. The Effect of Unfractionated Heparin Administration Timing on Radial Artery Spasm and Occlusion in Radial Coronary Angiography OP-43. The Mediating Role of Heart Rate in the Relationship Between Smoking and Myocardial Performance Op-44. Avoiding Emergency Surgery with Imaging-Guided Thrombolysis in Mechanical Valve Thrombosis OP-45. Predictive Value of the Frontal QRS-T Angle for Coronary Thrombus Burden in Patients Presenting with Acute Myocardial Infarction OP-46. STEMI Caused by Thrombotic Subclavian Occlusion in LIMA Grafted Patient OP-47. Hemoptysis During Cardioverter-Defibrillator Implantation: A Rare Complication OP-48. Intra-Arterial Lidocaine for Resistant Radial Artery Spasm OP-49. Routine Clinical and Lipid Parameters Predict High-Grade Atrioventricular Block After Transcatheter Aortic Valve Implantation: A Pragmatic Single-Center Study OP-50. CONUT Score and Length of Hospital Stay in Acute Decompensated Heart Failure OP-51. Distinction Between Type 2 Myocardial Infarction and Myocardial Injury in Troponin Positivity: Retrospective Clinical Classification and 30-Day Prognosis OP-52. Myocardial Contraction Fraction as an Independent Predictor of Cardiovascular Mortality in Patients with Chronic Renal Failure OP-53. Surgical Stentectomy and Bypass in Coronary Full Metal Jacket OP-54. AF-Ablation Performed via Transeptal Passage Through Septal Occuder Device: A Case Report. OP-55. Acute Axillary Artery Occlusion Following Transradial Intervention: A Case Report OP-56. A Multidomain Risk Cluster for Predicting Contrast-Induced Nephropathy After Carotid Artery Stenting OP-57. An Overlooked Phenotype: Widespread Non-calcified Atherosclerosis Presenting with Vision Loss OP-58. Safety and Efficacy of Carotid Artery Stenting Without Routine Anticholinergic Pretreatment OP-59. The Dark Path of Infective Endocarditis: Prosthetic Valve Endocarditis Unveiled by Multimodality Imaging OP-60. The Cost of Pregnancy? Peripartum Cardiomyopathy Following IVF OP-61. Malignant RCA in the Shadow of Perimyocarditis Op-62. One Implantation, Two Challenges: Anatomical Difficulty and Post-Cardiac Injury Syndrome OP-63. Ozaki Procedure OP-64. Diagnostic Performance of Coronary CT Angiography Compared with Invasive Coronary Angiography and the Impact of Coronary Calcium Score: A Single-Center Real-World Study